Multi-Project Scheduling Cost Optimization in a Machine Manufacturer Engineer-to-Order - Farizal, Farizal; Rachman, Amar; Tandean, Tifani; Sudarto, Sumarsono; Takahashi, Katsuhiko (UI Scholars Hub, 2016)
This paper discusses the utilization of mixed integer linear programming (MILP) model to optimize cost for multiproject scheduling in a machine maker company. The objective is to minimize total project’s penalty cost and labor cost. The model formulated shows how to achieve the objective i.e. whether to use outsourcing or overtime to finish all projects. The model of multi-project scheduling was solved by Branch & Bound algorithm coded in Lingo 14.0 software. The case study shows that if a company wants to minimize lateness, it should use overtime instead of outsourcing, which minimize total lateness of projects by 144 days or 73.5%. Whereas, if a company wants to optimize cost, they should use outsourcing instead of overtime, which reduces total cost of about 10,873,000 IDR or 28.5%. These results indicate that the model developed is applicable for optimizing multi-project scheduling.